Evolutionary history of hunter-gatherer marriage practices. - Robert S Walker (Public Library of Science (PLoS), 2011)
Background The universality of marriage in human societies around the world suggests a deep evolutionary history of institutionalized pair-bonding that stems back at least to early modern humans. However, marriage practices vary considerably from culture to culture, ranging from strict prescriptions and arranged marriages in some societies to mostly unregulated courtship in others, presence to absence of brideservice and brideprice, and polyandrous to polygynous unions. The ancestral state of early human marriage is not well known given the lack of conclusive archaeological evidence. Methodology Comparative phylogenetic analyses using data from contemporary hunter-gatherers around the world may allow for the reconstruction of ancestral human cultural traits. We attempt to reconstruct ancestral marriage practices using hunter-gatherer phylogenies based on mitochondrial DNA sequences. Results Arranged marriages are inferred to go back at least to first modern human migrations out of Africa. Reconstructions are equivocal on whether or not earlier human marriages were arranged because several African hunter-gatherers have courtship marriages. Phylogenetic reconstructions suggest that marriages in early ancestral human societies probably had low levels of polygyny (low reproductive skew) and reciprocal exchanges between the families of marital partners (i.e., brideservice or brideprice). Discussion Phylogenetic results suggest a deep history of regulated exchange of mates and resources among lineages that enhanced the complexity of human meta-group social structure with coalitions and alliances spanning across multiple residential communities.